Pedagogi Konstruktivisme dalam Praksis Pendidikan Indonesia - Euis Nurhidayati (Universitas Mathla'ul Anwar Banten, 2017)
Constructivism is one of philosophy of knowledge that emphasizes that our knowledge is (shapes) construction of ourselves. Knowledge is not an idea of reality. Knowledge is always a result of cognitive construction of reality by one’s activities. Some psychologists who started on constructivism approach are Piaget and Vygostky. The difference between them is where Piaget more emphasizes and discusses constructivism of learning process personally but Vygostky develops constructivism of learning process socially. Both of Individual Cognitive Constructivist and Sociocultural Constructivist dominate the constructivism concept. Constructivism learning consider that student continuously examine new information which contrast with old rule and revise the rule it is no longer appropriate. For encouraging student more active involve in learning process, it is should that: 1) learning atmosphere is democratic; 2) learning activities goes interactively and student-centered; 3) teacher encourages student to learn autonomously and responsible for their learning activities. Looking at the education practice in Indonesia, the concept constructivism is not implemented yet, although its concept is purposed, for example in KTSP (Kurikulum Tingkat Satuan Pendidikan) that clearly gives freedom to education units included teachers to build student competency that suitable with student needs and interest. One of some main problems of in learning in formal education (school) recently is lowness of student absorption. It was showed by student result learning average that still bad. This is of course a result of learning process that still conventional and far to touch student dimension, it means how actually learning is.